Analysts consensus before and during the financial crisis: evidence on the spanish market (mercado continuo) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
The goal of this article is to determine the effects of financial analysts’ consensus in the Spanish Stock Market (Mercado Continuo) in different periods (2002-2007 and 2008-2009), specifically its influence during the financial crisis. This article concludes that the effects of financial analysts’ consensus is modest but statistically significant in the Spanish Mercado Continuo, and is also stronger during the financial crisis.
Keywords: financial analyst; consensus estimates; target price; earning forecast; analyst recommendation.